Dynamic multi-technology production-inventory problem with emissions trading. Issue 2 (1st February 2016) - Zhang, Wei; Hua, Zhongsheng; Xia, Yu; Huo, Baofeng
ABSTRACT: We study a periodic-review multi-technology production-inventory problem of a single product with emissions trading over a planning horizon consisting of multiple periods. A manufacturer selects among multiple technologies with different unit production costs and emissions allowance consumption rates to produce the product to meet independently distributed random market demands. The manufacturer receives an emissions allowance at the beginning of the planning horizon and is allowed to trade allowances through an outside market in each of the following periods. To solve the dynamic multi-technology production-inventory problem, we virtually separate the problem into an inner layer and an outer layer. Based on the structural properties of the two layers, we find that the optimal emissions trading policy follows a target interval policy with two thresholds, whereas the optimal production policy has a composite base-stock structure. Our theoretical results show that no more than two technologies should be selected simultaneously at any state. However, different groups of technologies may be selected at different states. Our numerical tests confirm that it can be economically beneficial for a manufacturer to maintain multiple available technologies.